High-resolution underwater laser spectrometer sensing provides new insights into methane distribution at an Arctic seepage site - Jansson, Pär; Triest, Jack; Grilli, Roberto; Ferré, Benedicte; Silyakova, Anna; Mienert, Jurgen; Chappellaz, Jérôme (Ocean Science, 2019)
Source at https://doi.org/10.5194/os-15-1055-2019. Methane (CH4) in marine sediments has the potential to contribute to changes in the ocean and climate system. Physical and biochemical processes that are difficult to quantify with current standard methods such as acoustic surveys and discrete sampling govern the distribution of dissolved CH4 in oceans and lakes. Detailed observations of aquatic CH4 concentrations are required for a better understanding of CH4 dynamics in the water column, how it can affect lake and ocean acidification, the chemosynthetic ecosystem, and mixing ratios of atmospheric climate gases. Here we present pioneering high-resolution in situ measurements of dissolved CH4 throughout the water column over a 400 m deep CH4 seepage area at the continental slope west of Svalbard. A new fast-response underwater membrane-inlet laser spectrometer sensor demonstrates technological advances and breakthroughs for ocean measurements. We reveal decametre-scale variations in dissolved CH4 concentrations over the CH4 seepage zone. Previous studies could not resolve such heterogeneity in the area, assumed a smoother distribution, and therefore lacked both details on and insights into ongoing processes. We show good repeatability of the instrument measurements, which are also in agreement with discrete sampling. New numerical models, based on acoustically evidenced free gas emissions from the seafloor, support the observed heterogeneity and CH4 inventory. We identified sources of CH4, undetectable with echo sounder, and rapid diffusion of dissolved CH4 away from the sources. Results from the continuous ocean laser-spectrometer measurements, supported by modelling, improve our understanding of CH4 fluxes and related physical processes over Arctic CH4 degassing regions